2018
DOI: 10.5935/abc.20180113
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise and Regulation of Intracellular Calcium in Cardiomyocytes of Hypertensive Rats

Abstract: BackgroundRegulation of intracellular calcium (Ca2+) in cardiomyocytes is altered by hypertension; and aerobic exercise brings benefits to hypertensive individuals.Objective To verify the effects of aerobic exercise training on contractility and intracellular calcium (Ca2+) transients of cardiomyocytes and on the expression of microRNA 214 (miR-214) in the left ventricle of spontaneously hypertensive rats (SHR).MethodsSHR and normotensive Wistar rats of 16 weeks were divided into 4 groups -sedentary hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
2
8
1
5
Order By: Relevance
“…However, the effects of aerobic interval training and digoxin on Ca 2 + handling and this association with myocardial intracellular proteins have been poorly investigated. Although the literature reports that physical exercise favours Ca 2 + transport and increased Ca 2 + availability for cardiac contractility [4,56,57], our data did not reveal effects of association between digoxin and aerobic interval training on protein expression of SERCA2a, PLB and calcineurin. In the current study, the absence of changes in Ca 2 + handling in healthy hearts by digoxin alone and/or associated to aerobic interval training could be related to lack of need to raise the intracellular Ca 2 + since the animals did not have any pathological condition as heart failure.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the effects of aerobic interval training and digoxin on Ca 2 + handling and this association with myocardial intracellular proteins have been poorly investigated. Although the literature reports that physical exercise favours Ca 2 + transport and increased Ca 2 + availability for cardiac contractility [4,56,57], our data did not reveal effects of association between digoxin and aerobic interval training on protein expression of SERCA2a, PLB and calcineurin. In the current study, the absence of changes in Ca 2 + handling in healthy hearts by digoxin alone and/or associated to aerobic interval training could be related to lack of need to raise the intracellular Ca 2 + since the animals did not have any pathological condition as heart failure.…”
Section: Discussioncontrasting
confidence: 99%
“…When evaluating the dynamic movements of the stomatognathic system, especially the usual clinical condition of chewing, it is known that to affect and regulate the contractility of the skeletal muscle, thin lament proteins respond to calcium (Ca 2 + ) [29,30] and high-intensity aerobic training. In addition, there is an increase in the availability of the divalent cation ion inside the cells [31], promoting a stimulus for the release of neurotransmitters, contracting the muscles with proliferation of potential of action [32] that assists in the dynamic functional performance of the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another study showed that in hypertensive rats, ET reduced systolic arterial pressure and increased the accessibility of intracellular Ca 2+ in myocytes of the left ventricle as well as the expression of miR-214 (Rodrigues et al, 2018). However, the results contradicted the author's expectations and data from previous research that revealed decreased miR-214 expression and increased expression of sarcoplasmic reticulum Ca 2+ -ATPase (SERCA2a), the main facilitator of Ca 2+ translocation from the cytosol to the sarcoplasmic reticulum (Melo et al, 2015).…”
Section: Exercise Mediates Protection Against Hypertensionmentioning
confidence: 99%